2017
DOI: 10.1002/chem.201702665
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ and Real‐time Monitoring of Mechanochemical Preparation of Li2Mg(NH2BH3)4 and Na2Mg(NH2BH3)4 and Their Thermal Dehydrogenation

Abstract: For the first time, in-situ monitoring of uninterrupted mechanochemical synthesis of two bimetallic amidoboranes, M 2 Mg(NH 2 BH 3 ) 4 (M = Li, Na), by means of Raman spectroscopy has been applied. This approach allowed real-time observation of key intermediate phases and a straightforward follow-up of the reaction course. Detailed analysis of time-dependent spectra revealed a two-step mechanism through MNH 2 BH 3 · NH 3 BH 3 adducts as key intermediate phases which further reacted with MgH 2 , giving M 2 Mg(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Abe et al . showed that hydrogen absorption of palladium can effectively be improved by ion bombardment . They used low energy ions (30–350 keV) of H + , He + , N + i Ar + with the fluence range between 10 14 –10 17 ions/cm 2 .…”
Section: Experimental Approach To Destabilization Of Hydrogen‐storagementioning
confidence: 99%
See 1 more Smart Citation
“…Abe et al . showed that hydrogen absorption of palladium can effectively be improved by ion bombardment . They used low energy ions (30–350 keV) of H + , He + , N + i Ar + with the fluence range between 10 14 –10 17 ions/cm 2 .…”
Section: Experimental Approach To Destabilization Of Hydrogen‐storagementioning
confidence: 99%
“…At the ambient temperature and pressure their capacities become very low. On the other hand, in aminoboranes,, borohydrides, and metal hydrides hydrogen is chemically bonded to the storage medium. Due to relatively high activation energy, the sorption in such kind of materials is usually not reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important advantages mechanochemical activation offers in the area of hydrogen storage, the physico‐chemical mechanisms laying behind this phenomenon and in particular the associated tribological activation effects remained poorly understood. Recently, several experimental techniques have been developed, which allow for in situ and real‐time monitoring the mechanochemical transformations during milling that bridges the gap in the mechanistic understanding of these complex processes . Tribological activation correspond to the sliding of one surface against another .…”
Section: Non‐thermal and Non‐straightforward Thermally Driven Methodsmentioning
confidence: 99%
“…Mechanical milling under diverse conditions (different type of mills [15][16][17], BPR [18][19][20], different milling atmospheres [21][22][23]) is widely used as a method to improve sorption kinetics of various hydrides [24][25][26][27][28] and mostly magnesium hydride MgH 2 [29][30][31][32][33]. Regarding MgH 2 , the most common way to improve sorption kinetics is mechanical milling with the addition of transition metals -TM (Nb, V, Ti, Mn, Fe, Co, Ni, Cu, Zn) [34][35][36][37] [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%